Transnational Networks and the Dynamics of Informal Workers at the Aruk Border, Sambas Regency, Indonesia - Fatmawati Mochtar; Syarifah Ema R; Dwi Surti J; Azizah Larasati; Titi Fajriati (Jurnal Sosiologi Nusantara, 2026)
Cross-border labor mobility is a continuously growing phenomenon in the Indonesia-Malaysia border region, particularly in the Aruk area of Sambas Regency, West Kalimantan, which shares a direct border with Sarawak. This study analyzes the role of transnational networks in shaping the dynamics of informal workers in the Aruk border zone of Indonesia. A qualitative approach with a case study design was employed, with the research site located in the area of the Aruk State Border Crossing Post (Indonesian: Pos Lintas Batas Negara (PLBN) Aruk) and surrounding villages. Data were collected through in-depth interviews, field observations, and documentation studies involving cross-border workers, migrant worker families, and local community figures. The findings indicate that from a border studies perspective, border zones function not merely as dividing lines between states but also as dynamic and productive social spaces that shape cross-national economic interactions. Transnational networks formed through kinship ties, shared ethnicity, and geographical proximity facilitate informal labor mobility. Social capital in the form of transnational networks serves as a resource that provides access to job information, trust, and support for migrant workers. Beyond serving as channels for distributing information, transnational networks also function as informal social protection mechanisms capable of reducing economic and social risks throughout the labor migration process. The dynamics of informal workers in the Aruk border area demonstrate that socially networked cross-border connectivity is a key factor in linking local communities to the labor market in Sarawak, while simultaneously strengthening the survival strategies of border communities within the context of regional economic inequality.